Type 1 Conventional CD103+ Dendritic Cells Control Effector CD8+ T Cell Migration, Survival, and Memory Responses During Influenza Infection - Ng, See Liang; Teo, Yi Juan; Setiagani, Yolanda Aphrilia; Karjalainen, Klaus; Ruedl, Christiane (Frontiers in Immunology, 2018)
Type 1 conventional CD103+ dendritic cells (cDC1) contribute significantly to the cytotoxic T lymphocyte (CTL) response during influenza virus infection; however, the mechanisms by which cDC1s promote CTL recruitment and viral clearance are unclear. We demonstrate that cDC1 ablation leads to a deficient influenza-specific primary CD8+ T cell response alongside severe pulmonary inflammation, intensifying susceptibility to infection. The diminished pulmonary CTL population is not only a consequence of reduced priming in the lymph node (LN), but also of dysregulated CD8+ T cell egression from the LN and reduced CD8+ T cell viability in the lungs. cDC1s promote S1PR expression on CTLs, a key chemokine receptor facilitating CTL LN egress, and express high levels of the T cell survival cytokine, IL-15, to support CTL viability at the site of infection. Moreover, cDC1 ablation leads to severe impairment of CD8+ T cell memory recall and cross-reactive protection, suggesting that cDC1 are not only involved in primary T cell activation, but also in supporting the development of effective memory CD8+ T cell precursors. Our findings demonstrate a previously unappreciated and multifaceted role of CD103+ DCs in controlling pulmonary T cell-mediated immune responses.